Correlation of Forced Vital Capacity and Peak Expiratory Flow Rate with Serum Estrogen and Progesterone Levels in Combined Oral Contraceptive Pill (COCP) User - Islam, Farhana; Rakib, Shaikh Adnan; Sultana, Nayma (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Combined oral contraceptive pill (COCP) is the most commonly used contraceptive method in Bangladesh. This COCP has some effects on different organs including the lungs. So, there may be a relationship between forced vital capacity (FVC) and peak expiratory flow rate (PEFR) with serum estrogen and progesterone levels in combined oral contraceptive pill (COCP) users. Objective: To observe the relationship between FVC and PEFR with serum estrogen and progesterone levels in combined oral contraceptive pill users (COCP-U). Methodology: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka between July 2017 and June 2018. A total of 30 apparently healthy young women, age ranged 20 to 30 years were included in this study, who were combined oral contraceptive pill users (COCP-U) for at least 6 months. Another 30 age and BMI matched combined oral contraceptive pill nonusers (COCP-NU) were also taken as control for comparison. FVC and PEFR of all the subjects were measured by using Digital Auto Spirometer (MINATO AS-507). Moreover, their serum estrogen and progesterone levels were done to observe their levels and also to observe the relationship between them if present. Statistical analysis was done by Independent t-test and Pearson’s Correlation Coefficient test. Result: Spirometric parameters like FVC and PEFR were significantly higher in COCP-U women than those of nonuser women. Moreover, the mean serum estrogen and progesterone levels were also significantly higher in COCP users in comparison to those of non-users. Here, FVC showed positive and PEFR showed negative correlation with serum estrogen level and FVC showed negative, PEFR showed positive correlation with serum progesterone level in COCP users, though the relationships were statistically non-significant. Conclusion: The positive correlation of FVC and PEFR with serum estrogen and progesterone indicates, that improvement of pulmonary function occurs in COCP-U due to its estrogen and progesterone contents, which may be by increasing the strength of the muscles along with decreased airway resistance. J Shaheed Suhrawardy Med Coll 2022; 14(1): 37-42